Entrepreneurship education and problem bases learning. - Reis, Carlos Sousa (2015)
In this paper we draw on the concept of Entrepreneurship Education and describe ESECD completion of the Budapest Agenda and its Progression Model for Initial Teacher Education. The concept of entrepreneurship and entrepreneurship education is discussed. We also present the reference documents on Entrepreneurship Education, but the main issue of the paper is to give an overview account of ESECD performance regarding the Progression Model for Initial Teacher Education (PMITE). In a scale of four points for twenty one items and a maximum of eighty four points, ESECD scores thirty two points, which means ten points under the average.